Динамика фракционного состава белков сыворотки крови полевки-экономки и закаспийской полевки. Сообщение I. Возрастная изменчивость - Рогатко, И.В. (Вестник зоологии, 1974)
When studying the intraspecies variability of Cricetidae, the peculiarities of age changes in the content of serum protein fractions were considered in Microtus oeconomus Pall. and M. transcaspicus Satun. These characters are established to be different in various seasons of the year for all four age groups in each investigated species of the Microtus genus.